Cathelicidin-derived antiviral peptide inhibits herpes simplex virus 1 infection - Guo, Xiaomin; An, Yanxing; Tan, Wanmin; Ma, Ling; Wang, Mingyang; Li, Juyan; Li, Binghong; Hou, Wei; Wu, Li (Frontiers in Microbiology, 2023)
Herpes simplex virus 1 (HSV-1) is a widely distributed virus. HSV-1 is a growing public health concern due to the emergence of drug-resistant strains and the current lack of a clinically specific drug for treatment. In recent years, increasing attention has been paid to the development of peptide antivirals. Natural host-defense peptides which have uniquely evolved to protect the host have been reported to have antiviral properties. Cathelicidins are a family of multi-functional antimicrobial peptides found in almost all vertebrate species and play a vital role in the immune system. In this study, we demonstrated the anti-HSV-1 effect of an antiviral peptide named WL-1 derived from human cathelicidin. We found that WL-1 inhibited HSV-1 infection in epithelial and neuronal cells. Furthermore, the administration of WL-1 improved the survival rate and reduced viral load and inflammation during HSV-1 infection via ocular scarification. Moreover, facial nerve dysfunction, involving the abnormal blink reflex, nose position, and vibrissae movement, and pathological injury were prevented when HSV-1 ear inoculation-infected mice were treated with WL-1. Together, our findings demonstrate that WL-1 may be a potential novel antiviral agent against HSV-1 infection-induced facial palsy.